Análise da distribuição espacial dos casos suspeitos de Dengue, Chikungunya e Zika no município de São Carlos-SP - Lima, Anete Medeiros de (Universidade Federal de São Carlos, 2018)
The aim of this study was to analyze the spatial distribution of suspected cases of Dengue Virus (DENV), Chikungunya Virus (CHIKV) and ZIKV Virus (ZIKV) and the relationship with socioenvironmental indicators of the city of São Carlos-SP. This is an ecological study with multiple measures of analysis. Secondary data from the Information System on Notifiable Diseases (SINAM) were used in the period from 2016 to 2017, in addition to data from the Brazilian Institute of Geography and Statistics (IBGE) of the last Demographic Census of 2010. The data were obtained after approval by the Research Ethics Committee of UFSCar. Descriptive statistics of the diseases were performed, followed by a bivariate analysis of the sociodemographic variables and their relationships with the independent variables (scholarity and race). The construction of the social-environmental indicators was processed using Statistica software version 12.0, using the Principal Component Analysis (PCA) technique. The suspected cases geocoding was achieved by exporting the Excel tables to Google's Fusion Tables. After the geocoding of the addresses by Fusion Tables, the list was imported to Google Earth Pro .The generation of thematic maps was performed by Arcgis software version 10.5. In 2016 and 2017, 4552 and 1114 suspected dengue cases were registered, respectively; 118 and 71 suspected cases of chikungunya and 59 and 8 suspected cases of zika.The arboviruses predominated in female patients, being dengue, 52.99% in 2016 and 49.82% in 2017; to chikungunya 70.34% in 2016 and 57.75% in 2017; and for zika 67.71% in 2016 and 62.50% in 2017. Regarding the age group in the analyzed period, 37.5% of the suspected cases of DENV, 38.6% of the suspected cases of CHIK and 62.7% of the suspected cases of ZIKV were concentrated in the age ranges of 21 to 30 years and 41 to 50 years.The bivariate analysis showed the highest rates of DENV, CHIKV and ZIKV in people with complete high school, incomplete higher education and complete higher education. In 2016, we highlight the highest rate of suspected cases of dengue, 290.94 suspected cases/10,000 inhabitants. registered in the Center weighting area; The Cidade Jardim weighting area had the highest rate of chikungunya, with 10.95 suspected cases/10,000 inhabitants. and also the highest rate of zika with 19.12 suspected cases/ 10,000 inhab. In 2017, the highest rate of dengue was reported in the Cidade Jardim weighting area with 52.91 suspected cases/10,000 inhabitants; The Jockey Club weighting area presented the highest rate of chikungunya and zika with respectively 7.66 suspected cases/10,000 inhabitants. and 1.41 suspected cases/10,000 inhabitants. The results showed high rates of suspected cases of arboviruses in weighted areas with appropriate social conditions and reduced rates in weighted areas with social. It was concluded that the profile of suspected cases of dengue, chikungunya and zika in the population of São Carlos – SP is not related to low socio-environmental indicators and that population dynamics and mobility related to the high flow of university students may influence the pattern of spatial distribution of arboviruses in the municipality.
Analysis of the spatial distribution of suspected cases of Dengue, Chikungunya and Zika in the municipality of São Carlos-SP
Keywords: Dengue; Chikungunya; Zika; Indicadores sociais; Análise espacial; Social indicators; Spatial analysis; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE::SAUDE COLETIVA::EPIDEMIOLOGIA